ELIMINATION OF PSEUDOMONAS AERUGINOSA FROM WATER SYSTEMS: A REVIEW - Ghorpade, Kabirdas B.; Suryawanshi, Milind; Shinde, Sharda M. (Journal of Biomedical and Pharmaceutical Research, 2019)
Pseudomonads free-living bacteria that live primarily in soil, seawater, and fresh water. They also colonize plants and animals. Pseudomonads can grow in distilled water also. Pseudomonas spp., ubiquitous Gram negative bacilli, are found in natural waters such as lakes and rivers. On account of their tolerance to a wide variety of physical conditions and minimal nutrition requirements, Pseudomonas also can colonize biofilms in manmade systems such as drinking water. Pseudomonas aeruginosa is a major human opportunistic pathogen species of this group, which can cause a wide range of infections. In this review we have discussed effect of Bacteria on human health and the methods to control the Pseudomonas aeruginosa in water system. Keywords: Pseudomonas aeruginosa, Bacteriophages, water decontamination, Copper-silver ionization, Ozone, Pathogens.